2019
DOI: 10.1002/jeab.540
|View full text |Cite
|
Sign up to set email alerts
|

Assessing functions of stimuli associated with rich‐to‐lean transitions using a choice procedure

Abstract: Under fixed-ratio schedules, transitions from more to less favorable conditions of reinforcement (richto-lean transitions) usually generate extended pausing. One possible explanation for this effect is that stimuli associated with rich-to-lean transitions are aversive and, thus, extended pausing functions as escape. The purpose of this study was to characterize further the aversive function of different transitions, and the stimuli associated with them, by allowing pigeons to choose to complete select ratios i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…It should be noted, however, that the relation of pausing to other indices of aversive control is not entirely clear. For example, studies that have arranged for the opportunity to escape or choose the stimulus conditions surrounding transitions have found that the opportunity to do so has not reliably changed pausing (Everly et al, 2014;Langford et al, 2019;Retzlaff, 2017). Retzlaff et al, for example, found that even when the escape key was pecked, the pigeons did so after a period of time comparable to the typical baseline pause.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It should be noted, however, that the relation of pausing to other indices of aversive control is not entirely clear. For example, studies that have arranged for the opportunity to escape or choose the stimulus conditions surrounding transitions have found that the opportunity to do so has not reliably changed pausing (Everly et al, 2014;Langford et al, 2019;Retzlaff, 2017). Retzlaff et al, for example, found that even when the escape key was pecked, the pigeons did so after a period of time comparable to the typical baseline pause.…”
Section: Discussionmentioning
confidence: 99%
“…Water and health grit were readily available in their home cages, which were located in a temperature‐controlled colony room with a 12:12 hr light/dark cycle. All subjects had previous experience responding on multiple FR FR schedules and procedures as reported in Retzlaff et al (2017) and Langford et al (2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extended pausing in discriminable rich-lean transitions has been shown to be a general phenomenon in the laboratory. It has been replicated with rats (Baron et al, 1992;Baron et al, 1999;Brewer et al, 2017;Galuska & Yadon, 2011;Sawyer et al, 2019;Wade-Galuska, et al, 2005), pigeons (Langford et al, 2019;Perone & Courtney, 1992;Retzlaff et al, 2017;Toegel, 2017), hens (Harris et al, 2012;Young et al, 2017), monkeys (Galuska et al, 2007), and humans (Williams et al, 2011). It has been shown to occur when the operational definitions of the rich and lean components are based on reinforcer magnitude (e.g., Perone & Courtney, 1992), reinforcer delay (e.g., Harris et al, 2012), response requirement (e.g., Baron et al, 1992), and response-force requirement (e.g., Wade-Galuska et al, 2005).…”
Section: List Of Figuresmentioning
confidence: 99%